Northern Shortfin Squid (Illex illecebrosus) Fishery Footprint on the Northeast US Continental Shelf - Lowman, Brooke A.; Jones, Andrew W.; Pessutti, Jeffrey P.; Mercer, Anna M.; Manderson, John P.; Galuardi, Benjamin (Frontiers in Marine Science, 2021)
Northern shortfin squid (Illex illecebrosus) have presented a challenge for fishery management because of their life history traits and broad population distribution. Shortfin squid are characterized by a short semelparous lifespan and high interannual variability in recruitment. Much of the stock is thought to reside outside of the boundaries of existing fisheries surveys and fishing effort. Based on the annual migration pattern and broad geographic distribution of shortfin squid, it is believed that the US fishery has not had a substantial impact on the stock; however, catches are viewed as tightly constrained by quotas. To better estimate the potential impact of fishing on the resource, we worked with industry representatives, scientists, and managers to assess the availability of the northern shortfin squid population occupying the surveyed area of the US continental shelf to the US fishery. Taking a novel analytical approach, we combine a model-based estimate of area occupied by shortfin squid with the empirical US commercial shortfin squid fishery footprint to produce estimates of the area of overlap. Because our method overestimates the fishery footprint and underestimates the full distribution of the species we suggest that our estimates of the overlap between the area occupied by the squid and the fishery footprint is a way to develop a conservative estimate of the potential fishery impact on the population. Our findings suggest a limited degree of overlap between the US fishery and the modeled area on the US continental shelf known to be occupied by the squid, with a range of 1.4 - 36.3%. The work demonstrates the value of using high-resolution, spatially-explicit catch and effort data in a species distribution model to inform management of short-lived and broadly distributed species, such as shortfin squid.